Characterization of methicillin‐resistant Staphylococcus pseudintermedius isolated from dogs and cats. (16th July 2013) - Bardiau, Marjorie; Yamazaki, Kazuko; Ote, Isabelle; Misawa, Naoaki; Mainil, Jacques G.
ABSTRACT: The aim of this study was to explore the presence of methicillin‐resistant Staphylococcus pseudintermedius (MRSP) in a collection of S. pseudintermedius strains isolated from dogs and cats with dermatitis in Japan and to compare their genotypic and phenotypic characteristics. Clonal relationships were determined by pulse field gel electrophoresis (PFGE), staphylococcal chromosomal cassette mec (SCC mec ) typing, and multilocus sequence typing (MLST). Biofilm formation assay was performed using safranin staining in microplates. Three virulence genes coding for S. intermedius exfoliative toxin and Panton‐Valentine leukocidin ( siet, lukS‐PV and lukF‐PV ) were searched for in a collection of strains. Antimicrobial resistance against 15 antibiotics was studied by a disc diffusion method. Twenty‐seven MRSP were isolated. According to PFGE results the isolates were not closely related except for a few strains. MLST showed that the strains belonged to five groups, ST71 and ST26 being the two most prevalent. Three types of SCC mec (II, II–III and V) were identified. All isolates were siet ‐positive but PVL ‐negative. Most strains (except for two) produced strong biofilm in tryptic soy broth with glucose. Seventy‐eight percent of the isolates were resistant or intermediate to twelve or more antibiotics. Our study demonstrates that the ST71 lineage is widespread in Japan and that ST26 could represent an emerging lineage. Moreover, most of our strains are capable of forming strong biofilm and possess siet gene, two virulence characteristics that probably help the bacteria to persist and spread. Finally, our MRSP strains show a strong resistance profile to antibiotics commonly used in veterinary medicine.